2021
DOI: 10.3233/ajw210016
|View full text |Cite
|
Sign up to set email alerts
|

The Status of Surface Water in West Tripura District, India: An Approach by Using Water Quality Index and Multivariate Statistical Technique

Abstract: The present investigation provides a better interpretation of surface water (rivers, ponds, bills, lakes, etc.) quality utilising entropy weighted water quality index (EWWQI) and different multivariate statistical techniques. Eleven physicochemical parameters including alkalinity, dissolved oxygen (DO), pH, total dissolved solids (TDS), electrical conductivity (EC), calcium (Ca), turbidity, magnesium (Mg), total hardness (TH), chloride (Cl-), and iron (Fe) were analysed and monitored at 23 sampling sites (in D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One of the most popular and widely used methods to determine water quality is WAWQI (Zait et al 2022 ; Ahmed et al 2021 ; Pradhan et al 2021 ; Roy and Manna 2021 ). Railway stations have been classified based on estimated WAWQI.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most popular and widely used methods to determine water quality is WAWQI (Zait et al 2022 ; Ahmed et al 2021 ; Pradhan et al 2021 ; Roy and Manna 2021 ). Railway stations have been classified based on estimated WAWQI.…”
Section: Resultsmentioning
confidence: 99%
“…Horton ( 1965 ) developed the weighted arithmetic water quality index (WAWQI) model and Brown et al ( 1970 ) modified it. Several researchers (Mahammad and Islam 2021 ; Menberu et al 2021 ; Ayogu et al 2020 ; Roy and Manna 2021 ; Adimalla and Qian 2019 ) used this method to calculate WAWQI, which has been computed using the following steps: …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies showed a transition to the use of different scientific methods, including the water quality index, pollution load index, and statistical techniques. A contemporary study, in Tripura, focused on covering various water bodies and using modern methods and advanced statistical tools [44][45][46][47]. In this study area, the authors applied different scientific methods: water quality index (WQI), and pollution load index (PLI), along with statistical analysis.…”
Section: Contemporary Researchmentioning
confidence: 99%
“…The Principal Component Analysis (PCA) is used to reveal the "hidden" factors controlling surface water quality [28][29][30][31][32]. Numerous groups of studies use both CA and PCA as additions to the WQI to introduce the specific outputs of both techniques to water quality assessment [11,[33][34][35][36][37][38][39]. To investigate the temporal behavior of water quality indicators at regions with pronounced seasonality, Discriminant Analysis (DA) is used [13,[40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%